Preparation method and application of single-layer MXene composite material

By preparing single-layer MXene composite materials, the problems of insufficient conductivity and stability of multi-layer MXene are solved, higher specific surface area and conductivity are achieved, and electrochemical signal response and material stability are significantly improved.

CN119349580APending Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411291795.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

In existing electrochemical sensors, the specific surface area of ​​the multi-layer MXene is limited and the electron transmission path is long, resulting in insufficient conductivity and signal response. At the same time, the functional groups at the edges of the nanosheets are prone to oxidation, resulting in poor performance stability.

Method used

Using the preparation method of single-layer MXene composite materials, the ternary layered compound MAX phase powder is dispersed in a mixture of hydrochloric acid and lithium fluoride, and the single-layer MXene nanometers are prepared through steps such as ultrasonic, centrifugation, water washing and vacuum drying. flakes, and mixed and calcined with inorganic salts of cobalt, inorganic salts of nickel and sugar carbon sources to form single-layer MXene nanomaterials coated with carbon-coated nickel-cobalt alloys, and then calcined and electropolymerized under a protective atmosphere to form polyaniline Modified composite materials.

Benefits of technology

The specific surface area and conductivity of the single-layer MXene composite material are increased, the electron transmission rate and electrochemical signal response are enhanced, the stability and acid and alkali resistance of the material are improved, the electrochemical signal is significantly improved, and the stability is also significantly improved. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349580A_ABST
    Figure CN119349580A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a single-layer MXene composite material, and belongs to the technical field of preparation of electrochemical sensor composite materials. The preparation method comprises the following steps: preparing single-layer MXene, loading carbon-coated nickel-cobalt alloy on the single-layer MXene, modifying the composite material on the surface of an electrode by using a dispensing method, and tightly attaching aniline on the carbon-coated nickel-cobalt alloy-single-layer MXene by using an electropolymerization method to obtain the conductive polymerized aniline-carbon-coated nickel-cobalt alloy-single-layer MXene sensing material. The characteristics of high conductivity of aniline, excellent specific surface area of single-layer MXene, stability of carbon layer coating and the like are combined, so that the conductivity and the stability of the composite material are greatly improved, signals of a sensor are easier to detect, and the current of a modified electrode is improved by more than 1.8 times compared with that of a bare electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of electrochemical sensor composite materials, and specifically relates to a preparation method and application of a single-layer MXene composite material. Background Art

[0002] Bio-small molecules are important substances in living organisms, and their detection is of great significance. Although traditional detection methods such as high performance liquid chromatography and spectrophotometry have accurate detection results, they are costly and have a limited detection range. Although electrochemical analysis makes up for the shortcomings of the above methods, the electrode molecule recognition ability of the electrochemical sensor itself is extremely weak, and the response signal is very low. Therefore, it is necessary to modify the electrode surface to improve the electrocatalytic activity of the electrode surface.

[0003] Although multilayer MXene is widely used in the field of electrochemical sensors due to its highly ordered layered structure, its specific surface area is limited, resulting in a longer electron transmission path, which is not conducive to improving the electron transmission rate and conductivity. In addition, the functional groups on the edge of MXene nanosheets are easily oxidized, causing the performance of electrochemical sensors to decline rapidly after long-term testing, resulting in poor stability.

[0004] The SCI document entitled Preparation of AuNPs / MXene nanocomposite for the electrochemical determination of dopamine improves the performance of the sensor by mixing multilayer MXene with gold nanocolloids. However, from the scan rate diagram of the effective area calculated in the article, it can be seen that the electrical signal at 0.1 mV / s is only 22 μA, indicating that the performance of multilayer MXene composited with other materials for electrochemical sensors needs to be improved. The Chinese invention patent document with publication number CN113552196A discloses a few-layer MXene-ionic liquid droplet modified electrode, its preparation method, and its application in the detection of Sudan red. The patent obtains an electrode modified material by simply mixing a few-layer MXene and an ionic liquid through ultrasonic oscillation, but the maximum current of its working curve does not exceed 2 μA, indicating that the conductivity of the composite material prepared by this method is still insufficient. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a single-layer MXene composite material and its application to solve the problems of weak electrochemical signals and poor stability of sensors.

[0006] In order to solve the above-mentioned technical problems, the present invention adopts the following technical solutions: On the one hand, the present invention provides a method for preparing a single-layer MXene composite material, comprising the following steps: (1) dispersing the ternary layered compound MAX phase powder in a mixture of hydrochloric acid and lithium fluoride, stirring and dispersing, then adding it to dimethyl sulfoxide and ultrasonicating, centrifuging, washing with water, and vacuum drying to obtain a single-layer MXene nanosheet; (2) adding an inorganic salt of cobalt, an inorganic salt of nickel, a sugar carbon source and a single-layer MXene nanosheet into deionized water, heating and stirring until a viscous state, vacuum drying, and calcining under a protective atmosphere to obtain a carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial; (3) dispersing the carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial in an isopropanol aqueous solution and ultrasonically dispersing it to prepare a dispersion, coating the dispersion on the surface of a glassy carbon electrode and drying it to obtain a carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial modified glassy carbon electrode; (4) Using aniline and sulfuric acid as electrolytes, the carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial-modified glassy carbon electrode was scanned by cyclic voltammetry in the voltage range of 0.5~1.0V, and the black substance on the surface of the glassy carbon electrode was collected and dried to obtain a single-layer MXene composite material.

[0007] Preferably, in the step (1), the ternary layered compound MAX phase powder is one of Ti3AlC2 powder or Nb4AlC3 powder or Ta4AlC3 powder or V4AlC3 powder, and the mass volume ratio of the ternary layered compound MAX phase powder, lithium fluoride and hydrochloric acid is 1g:0.222~0.666g:3~10mL; the concentration of hydrochloric acid is 4~8M, the stirring temperature is 20~30℃, the stirring time is 8~24h, the ultrasonic time is 1~3h, the centrifugal time is 3~5min / time, the number of centrifugal water washings is 3~5 times, the vacuum drying temperature is 40~60℃, and the drying time is 12~20h.

[0008] Preferably, in the step (2), the inorganic salt of cobalt is one of cobalt chloride, cobalt nitrate, cobalt acetate or cobalt sulfate, the inorganic salt of nickel is one of nickel chloride, nickel nitrate, nickel acetate or nickel sulfate, the carbohydrate carbon source is one of glucose, sucrose, fructose or starch, the mass ratio of the inorganic salt of cobalt, the inorganic salt of nickel, the carbohydrate carbon source and the monolayer MXene nanosheet is 1~2:2~5:1:1, the protective atmosphere is nitrogen or argon, the calcination temperature is 500~800°C, the heating rate is 2~10°C / min, and the holding time is 4~8h.

[0009] Preferably, in the step (4), the volume ratio of aniline to sulfuric acid is 1:1, the number of cyclic voltammetry scans is 10 to 20, the scan rate is 100 mV / s, the drying temperature is 60 to 80° C., and the drying time is 4 to 8 h.

[0010] In another aspect, the present invention provides a use of the above material in an electrochemical sensor.

[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The technical solution of the present invention adopts the method of in-situ HF etching, centrifugation and dimethyl sulfoxide intercalation to prepare a single-layer MXene nanosheet with a length of about 1.0~1.5μm and a thickness of about 50~100nm. Compared with multi-layer MXene, the single-layer MXene nanosheet has a larger specific surface area and a shorter electron transmission path, and the single-layer sheet structure is more conducive to the loading of other conductive materials such as carbon, thereby improving the electron transmission rate and the electrochemical signal of the sensor.

[0012] 2. The method of the present invention obtains a carbon-coated nickel-cobalt alloy-loaded single-layer MXene nanosheet by mixing and calcining an inorganic salt of cobalt, an inorganic salt of nickel, and a sugar carbon source with a single-layer MXene nanosheet. When the composite material does not have the nickel-cobalt alloy, the current is only increased by 14.9 μA, which indicates that the nickel-cobalt alloy can promote electron transfer and enhance the conductivity of the composite material and the activity of the electrode. At the same time, the carbon layer can form a protective layer to alleviate the decomposition of the composite material, and the stability of the composite material without the carbon layer decreases by 20.5%. Since the carbon layer itself also has good conductivity and acid and alkali resistance, the composite material has more excellent stability while the conductivity is significantly increased.

[0013] 3. The present invention polymerizes aniline monomers on the surface of the carbon-coated nickel-cobalt alloy under the action of an external electric field, and obtains polyaniline by controlling the voltage, scanning number, etc. When the composite material does not have polyaniline, the current only rises by 14.4 μA, which indicates that the high conductivity of polyaniline also improves the signal of the electrochemical sensor.

[0014] 4. The method of electropolymerization of aniline in the present invention is convenient, efficient, and the thickness of aniline is highly controllable. The obtained modified electrode can be directly used for electrochemical detection, eliminating the filtration, drying and other operation steps of the oxidation method, and provides a new method for improving the electrochemical signal of the sensor.

[0015] 5. In summary, the single-layer MXene composite material prepared by the method of the present invention performs outstandingly in the application of electrochemical sensors. In potassium ferrocyanide characterization solution, the electrical signal of the multilayer MXene composite material in the reference at 0.1mV / s is 22μA, while the electrical signal of the single-layer MXene composite material at 0.1mV / s is 38.8μA, which is 1.7 times that of the multilayer MXene composite material, and the electrochemical signal is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope (SEM) image of a single-layer MXene composite material prepared in Example 1 at a scale of 1 μm; Figure 2For comparison, the scanning electron microscope (SEM) image of multilayer MXene at 1 μm scale in the literature Preparation of AuNPs / MXene nanocomposite for the electrochemical determination of dopamine; Figure 3 This is the cyclic voltammetry (CV) diagram of the single-layer MXene composite material / GCE modified electrode prepared in Example 1 measured in the characterization solution.

[0017] Figure 4 This is the X-ray diffraction pattern (XRD) of the single-layer MXene composite material in Example 1. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the embodiments and comparative examples, but the present invention is not limited thereto. Example 1

[0019] (1) 1 g Ti3AlC2 powder was dispersed in a mixed solution of 10 ml 6 M HCl and 0.666 g LiF, stirred and dispersed at 30 °C for 24 h, then added to dimethyl sulfoxide and ultrasonicated for 2 h, centrifuged for 3 min / time, washed with water 3 times and vacuum dried at 50 °C for 12 h to obtain a single layer Ti3C2T x Nanosheets; (2) Cobalt nitrate, nickel nitrate, sucrose and the single-layer Ti3C2T obtained in step (1) are added to the x The nanosheets were added to deionized water, heated and stirred until viscous, dried at 60 °C in vacuum for 12 h, and then heated to 800 °C at a heating rate of 5 °C / min under argon protection and calcined for 6 h to obtain C@NiCo-Ti3C2T x Nanomaterials, Cobalt Nitrate, Nickel Nitrate, Sucrose and Monolayer Ti3C2T x The mass ratio of nanosheets is 2:5:1:1; (3) The C@NiCo-Ti3C2T obtained in step (2) above x The nanomaterials were dispersed in a mixture of isopropanol and water and ultrasonically dispersed to prepare a 1.5 mg / mL dispersion. 1.0 μL was applied to the surface of a glassy carbon electrode and dried to obtain C@NiCo-Ti3C2T x / GCE modified electrode, the volume ratio of isopropanol and water was 1:1; (4) Using aniline and sulfuric acid as electrolyte, the C@NiCo-Ti3C2T x The PANI-C@NiCo-Ti3C2T / GCE modified electrode was obtained by cyclic voltammetry scanning for 20 cycles in the voltage range of 0.5~1.0V. x / GCE, the black material on the surface of the glassy carbon electrode was collected and dried at 80 °C for 6 h to obtain a single-layer MXene composite material (PANI-C@NiCo-Ti3C2T x ), the molar ratio of aniline to sulfuric acid is 1:1.

[0020] The single-layer MXene composite material (PANI-C@NiCo-Ti3C2T x ), and its electrochemical performance was characterized by cyclic voltammetry. Compared with the bare glassy carbon electrode, PANI-C@NiCo-Ti3C2T x The current of the / GCE modified electrode is 38.8μA, while the current of the bare electrode is 17.2μA, an increase of 21.6μA. Example 2

[0021] (1) 1 g Nb4AlC3 powder was dispersed in a mixed solution of 3 mL 4 M HCl and 0.222 g LiF, stirred and dispersed at 25 °C for 16 h, then added to dimethyl sulfoxide and ultrasonicated for 1 h, centrifuged for 5 min / time, washed with water 5 times and vacuum dried at 40 °C for 20 h to obtain a single layer Nb4C3T x Nanosheets; (2) Cobalt chloride, nickel chloride, glucose and the single layer Nb4C3T obtained in step (1) are added to the x The nanosheets were added to deionized water, heated and stirred until viscous, dried at 80 °C in vacuum for 8 h, and then calcined at 800 °C for 4 h at a heating rate of 2 °C / min under nitrogen protection to obtain C@NiCo-Nb4C3T x Nanomaterials, cobalt chloride, nickel chloride, glucose and monolayer Nb4C3T x The mass ratio of nanosheets is 1:5:1:1; (3) C@NiCo-Nb4C3T obtained in step (2) above x The nanomaterials were dispersed in a mixed solution of isopropanol and water and ultrasonically prepared into a 1.5 mg / mL dispersion. 1.0 μL was applied to the surface of a glassy carbon electrode and dried to obtain C@NiCo-Nb4C3T x / GCE modified electrode, the volume ratio of isopropanol and water was 1:1; (4) Using aniline and sulfuric acid as electrolyte, the C@NiCo-Nb4C3T x / GCE was scanned by cyclic voltammetry for 10 cycles in the voltage range of 0.5~1.0V to obtain PANI-C@NiCo-Nb4C3T x / GCE, collect the black material on the surface of the glassy carbon electrode and dry it at 60 °C for 4 h to obtain a single-layer MXene composite material (PANI-C@NiCo-Nb4C3Tx ), the molar ratio of aniline to sulfuric acid is 1:1.

[0022] The single-layer MXene composite material (PANI-C@NiCo-Nb4C3T x ), and its electrochemical performance was characterized by cyclic voltammetry. Compared with the bare glassy carbon electrode, PANI-C@NiCo-Nb4C3T x The current of the / GCE modified electrode was 38.4 μA, while the current of the bare electrode was 18.2 μA, an increase of 20.2 μA. Example 3

[0023] (1) 1 g Ta4AlC3 powder was dispersed in a mixed solution of 6 mL 8 M HCl and 0.444 g LiF, stirred and dispersed at 20 °C for 8 h, then added to dimethyl sulfoxide and ultrasonicated for 3 h, centrifuged for 4 min / time, washed with water 4 times and vacuum dried at 60 °C for 12 h to obtain a single layer of Ta4C3T x Nanosheets; (2) Cobalt acetate, nickel acetate, fructose and the monolayer Ta4C3T obtained in step (1) are added to the mixture. x The nanosheets were added to deionized water, heated and stirred until viscous, dried at 60 °C in vacuum for 8 h, and then calcined at 500 °C for 8 h at a heating rate of 8 °C / min under argon protection to obtain C@NiCo-Ta4C3T x Nanomaterials, Cobalt Acetate, Nickel Acetate, Fructose and Monolayer Ta4C3T x The mass of the nanosheets is 1:2:1:1; (3) C@NiCo-Ta4C3T obtained in step (2) above x The nanomaterials were dispersed in a mixed solution of isopropanol and water and ultrasonically prepared into a 1.5 mg / mL dispersion. 1.0 μL was coated on the surface of a glassy carbon electrode and dried to obtain C@NiCo-Ta4C3T x / GCE modified electrode, the volume ratio of isopropanol and water was 1:1; (4) Using aniline and sulfuric acid as electrolyte, the C@NiCo-Ta4C3T x / GCE was scanned by cyclic voltammetry for 15 cycles in the voltage range of 0.5~1.0V to obtain PANI-C@NiCo-Ta4C3T x / GCE, collect the black material on the surface of the glassy carbon electrode and dry it at 70 °C for 8 h to obtain a single-layer MXene composite material (PANI-C@NiCo-Ta4C3T x ), the molar ratio of aniline to sulfuric acid is 1:1.

[0024] The single-layer MXene composite material (PANI-C@NiCo-Ta4C3T x ), and its electrochemical performance was characterized by cyclic voltammetry. Compared with the bare glassy carbon electrode, PANI-C@NiCo-Ta4C3T x The current of the / GCE modified electrode was 39.1 μA, while the current of the bare electrode was 18.1 μA, an increase of 21.0 μA. Example 4

[0025] (1) 1 g of V4AlC3 powder was dispersed in a mixed solution of 10 mL of 6 M HCl and 0.666 g of LiF, stirred and dispersed at 25 °C for 24 h, then added to dimethyl sulfoxide and ultrasonicated for 2 h, centrifuged for 5 min / time, washed with water 5 times, and dried at 50 °C for 16 h to obtain a single layer of V4C3T x Nanosheets; (2) Cobalt sulfate, nickel sulfate, starch and the single-layer V4C3T obtained in step (1) x The nanosheets were added to deionized water, heated and stirred until viscous, dried at 80 °C in vacuum for 12 h, and then calcined at 600 °C for 7 h at a heating rate of 10 °C / min under nitrogen protection to obtain C@NiCo-V4C3T x Nanomaterials, cobalt sulfate, nickel sulfate, starch and monolayer V4C3T x The mass ratio of nanosheets is 1:3:1:1; (3) C@NiCo-V4C3T obtained in step (2) above x The nanomaterials were dispersed in a mixed solution of isopropanol and water and ultrasonically prepared into a 1.5 mg / mL dispersion. 1.0 μL was applied to the surface of a glassy carbon electrode and dried to obtain C@NiCo-V4C3T x / GCE modified electrode, the volume ratio of isopropanol and water was 1:1; (4) Using aniline and sulfuric acid as electrolyte, the C@NiCo-V4C3T x / GCE was scanned by cyclic voltammetry for 20 cycles in the voltage range of 0.5~1.0V to obtain PANI-C@NiCo-V4C3T x / GCE, the black material on the surface of the glassy carbon electrode was collected and dried at 80 °C for 6 h to obtain a single-layer MXene composite material (PANI-C@NiCo-V4C3T x ), the molar ratio of aniline to sulfuric acid is 1:1.

[0026] The single-layer MXene composite material (PANI-C@NiCo-V4C3T x), and its electrochemical performance was characterized by cyclic voltammetry. Compared with the bare glassy carbon electrode, PANI-C@NiCo-V4C3T x The current of / GCE is 38.2μA, while the current of bare electrode is 17.5μA, which is an improvement of 20.7μA. Comparative Example 1

[0027] In this comparative example, no nickel inorganic salt and cobalt inorganic salt were added when preparing the composite material, and the other processes were consistent with those of Example 1. The current of the PANI-C / GCE modified electrode was 32.0 μA, while the current of the bare electrode was 17.1 μA, an increase of 14.9 μA. Comparative Example 2

[0028] In this comparative example, no sugar carbon source was added when preparing the composite material, and the other processes were consistent with those in Example 1. x The current of the / GCE modified electrode was 29.8 μA, while the current of the bare electrode was 16.8 μA, an increase of 13.0 μA. Comparative Example 3

[0029] In this comparative example, aniline polymerization was not performed when preparing the composite material, and the other processes were consistent with those in Example 1. x The current of the / GCE modified electrode was 31.0 μA, while the current of the bare electrode was 16.6 μA, an increase of 14.4 μA. Test Example 1

[0030] PANI-C@NiCo-Ti3C2T prepared in Example 1 x The electrochemical sensing materials were subjected to morphology (SEM) testing and X-ray diffraction (XRD) testing.

[0031] PANI-C@NiCo-Ti3C2T obtained in Example 1 x Electrochemical sensing materials were tested by SEM, and the results are as follows Figure 1 As shown in the figure, it can be seen that the single-layer Ti3C2T x Nanosheets were successfully prepared, and single-layer Ti3C2T x Nanosheets, length is about 1.0~1.5μm, thickness is about 50~100nm. The composite material is based on a single layer of MXene nanosheets, carbon-coated nickel-cobalt alloy and granular polyaniline attached to the surface loaded on MXene, the length of the polyaniline is about 0.3~0.5μm. PANI-C@NiCo-Ti3C2T x The composite material provides excellent electrochemical performance for electrochemical sensors and significantly enhances the electrical signal.

[0032] from Figure 4 It can be seen that the characteristic peak of MXene appears near 7.5°, the characteristic peak of polyaniline near 16°, and the characteristic peaks of nickel-cobalt alloy (45°, 52°) verify that PANI-C@NiCo-Ti3C2T x Successful synthesis of composite materials. Application Example 1

[0033] The materials obtained in the above embodiments and comparative examples are used for detecting electrochemical signals in an electrochemical sensor, and the steps are as follows: (1) Blow dry the liquid on the surface of the modified electrode with an inert gas; (2) placing the above electrode in a mixed solution of 0.1 mmol / L K3[Fe(CN)6] and 1.0 mol / L KCl for cyclic voltammetry scanning; The scanning parameters were set as follows: the interval potential on the CHI660E workstation was 0.7~-0.3V, the scanning speed was 100mV / s, the number of scanning circles was 4, the interval was 0.001V, and the sensitivity was 1.0×10 -4 A / V.

[0034]

[0035] The electrochemical signals of the electrochemical sensors of different embodiments and reference examples were compared, and the results are shown in Table 1. In a mixed electrolyte of 0.1 mmol / L K3[Fe(CN)6] and 1.0 mol / L KCl, the current of Example 1 was 38.8 μA by cyclic voltammetry, while the current of the bare electrode was only 17.2 μA, which was increased by 21.6 μA, indicating that the prepared PANI-C@NiCo-Ti3C2T x It has excellent electrochemical signals (Table 1). In addition, the same tests were performed on the materials of Examples 2 to 4, and the currents were greatly improved, indicating that the composite materials prepared by the method of the present invention have very excellent electrical conductivity. Although the electrochemical signal of the multilayer MXene composite material in the reference has been improved (5.3μA), the increase in current is far less than the increase in the electrochemical signal of the single-layer MXene nanosheet on the sensor in the present invention. This is because the single-layer MXene nanosheet has a high specific surface area and a shorter electron transmission path, thereby improving the electrochemical signal of the sensor. It can be seen from Comparative Examples 1 to 3 that when no carbohydrate carbon source, inorganic salts of cobalt and inorganic salts of nickel and polyaniline are added, although the electrical signal of the sensor is improved, the increase in current amplitude does not exceed 15μA, indicating that these three also provide conductivity for the sensor.

[0036]

[0037] From the stability data in Table 2, it can be seen that when the composite material does not have nickel-cobalt alloy, the stability of the electrochemical sensor drops to 15.9%, and when it is not coated with a carbon layer, the stability drops to 20.5%. This is because the nickel-cobalt alloy can play a synergistic role in increasing the stability of the composite material, while the carbon layer coating forms a protective layer that can alleviate the decomposition of the composite material and make the sensor have better acid and alkali resistance and organic solvent resistance, so that the single-layer MXene composite material / GCE electrochemical sensor has better stability.

[0038] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a single-layer MXene composite material, characterized in that: The following steps are involved: (1) dispersing the ternary layered compound MAX phase powder in a mixture of hydrochloric acid and lithium fluoride, stirring and dispersing, then adding it to dimethyl sulfoxide and ultrasonicating, centrifuging, washing with water, and vacuum drying to obtain a single-layer MXene nanosheet; (2) adding an inorganic salt of cobalt, an inorganic salt of nickel, a sugar carbon source and a single-layer MXene nanosheet into deionized water, heating and stirring until a viscous state, vacuum drying, and calcining under a protective atmosphere to obtain a carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial; (3) dispersing the carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial in an isopropanol aqueous solution and ultrasonically dispersing it to prepare a dispersion, coating the dispersion on the surface of a glassy carbon electrode and drying it to obtain a carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial modified glassy carbon electrode; (4) Using aniline and sulfuric acid as electrolytes, the carbon-coated nickel-cobalt alloy-single-layer MXene nanomaterial-modified glassy carbon electrode was scanned by cyclic voltammetry in the voltage range of 0.5~1.0V, and the black substance on the surface of the glassy carbon electrode was collected and dried to obtain a single-layer MXene composite material.

2. The method for preparing a single-layer MXene composite material according to claim 1, characterized in that: In the step (1), the ternary layered compound MAX phase powder is one of Ti3AlC2 powder, Nb4AlC3 powder, Ta4AlC3 powder or V4AlC3 powder; the mass volume ratio of the ternary layered compound MAX phase powder, lithium fluoride and hydrochloric acid is 1g:0.222~0.666g:3~10mL; the concentration of hydrochloric acid is 4~8M, the stirring temperature is 20~30℃, the stirring time is 8~24h, the ultrasonic time is 1~3h, the centrifugal time is 3~5min / time, the number of centrifugal water washings is 3~5 times, the vacuum drying temperature is 40~60℃, and the drying time is 12~20h.

3. The method for preparing a single-layer MXene composite material according to claim 1, characterized in that: In the step (2), the inorganic salt of cobalt is one of cobalt chloride, cobalt nitrate, cobalt acetate or cobalt sulfate, the inorganic salt of nickel is one of nickel chloride, nickel nitrate, nickel acetate or nickel sulfate, the carbohydrate carbon source is one of glucose, sucrose, fructose or starch, the mass ratio of the inorganic salt of cobalt, the inorganic salt of nickel, the carbohydrate carbon source and the monolayer MXene nanosheet is 1~2:2~5:1:1, the protective atmosphere is nitrogen or argon, the calcination temperature is 500~800°C, the heating rate is 2~10°C / min, and the holding time is 4~8h.

4. The method for preparing a single-layer MXene composite material according to claim 1, characterized in that: In the step (4), the molar ratio of aniline to sulfuric acid is 1:1, the number of cyclic voltammetry scans is 10 to 20, the scan rate is 100 mV / s, the drying temperature is 60 to 80° C., and the drying time is 4 to 8 hours.

5. An application of the single-layer MXene composite material as claimed in claim 4, characterized in that: The single-layer MXene composite material is used in an electrochemical sensor.

Citation Information

Patent Citations

  • Few-layer MXene-ionic liquid droplet modified electrode as well as preparation method and application thereof in detection of Sudan red

    CN113552196A